2019
DOI: 10.1002/cam4.2170
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a new staging system for node‐negative gastric cancer based on recursive partitioning analysis: An international multi‐institutional study

Abstract: Background Whether the tumor‐node‐metastasis (TNM) staging system is appropriate for patients with node‐negative gastric cancer (GC) is still inconclusive. The modified staging system developed by recursive partitioning analysis (RPA) showed good prognostic performance in a variety of cancers. The application of RPA has not been reported in the prognostic prediction of GC. Methods Node‐negative GC patients who underwent radical resection at Fujian Medical University Union Hospital (n = 862) and Sun Yat‐sen Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Recently, nomograms have been used for tumor prognosis prediction models after NAT [11][12][13][14][15][16]. These models show superior performance compared to conventional staging models [17][18][19][20][21]. Most studies analyzing prognosis of individuals who underwent treatment and follow-ups use nomograms.…”
Section: Ivyspringmentioning
confidence: 99%
“…Recently, nomograms have been used for tumor prognosis prediction models after NAT [11][12][13][14][15][16]. These models show superior performance compared to conventional staging models [17][18][19][20][21]. Most studies analyzing prognosis of individuals who underwent treatment and follow-ups use nomograms.…”
Section: Ivyspringmentioning
confidence: 99%
“…The placement of some pN3a patients was revised into stage IIIB, and pT3-4bN3bM0 was classified as stage IIIC [12]. Although previous studies have confirmed the prognostic value of the 8th AJCC stage system for gastric cancer (GC), it is mostly confined to patients with stage III [31], lymph node negative or lymph node the 15-Lymph Node Minimum [32,33]. Our study firstly evaluated the prognostic value of the 8th AJCC stage system for resectable GC from multicenter database.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Lin and colleagues conceptualized the application of recursive partition analysis in the prognostic prediction of node-negative gastric cancer. The tool produced superior outcomes than the AJCC [ 63 ]. A nomogram based on T stage, N stage, comprehensive treatment, age at diagnosis, grade, and tumor size performs better in the individualized prediction of survival among patients with resectable disease, including stage III/IV patients [ 64 ].…”
Section: Validation Of the 8th Ajcc Tnm Staging Systemmentioning
confidence: 99%